2014
DOI: 10.5539/ies.v7n11p84
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Teaching Competencies to Enhance Students’ EFL Learning at Taif University

Abstract: The paper aimed to investigate the teaching competencies implemented by instructors to enhance EFL students at Taif University in Saudi Arabia. The first two questions discussed the degree of implementing the teaching competencies, which either enhance or hinder learning. The third and fourth questions were an attempt to examine if there were any significant differences at (=0.05) due to instructors' qualifications and years of experience. The researcher developed an observation checklist to investigate the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, Tawalbeh and Ismail (2014) confirmed that teachers' competency related to review/assessment was rarely or not demonstrated. The results further revealed that teachers have low performance in utilizing varied assessment tools, keeping accurate records, analyzing students' performance and giving feedback, and developing and implementing appropriate activities based on assessment results to promote learning.…”
Section: Introductionmentioning
confidence: 74%
“…However, Tawalbeh and Ismail (2014) confirmed that teachers' competency related to review/assessment was rarely or not demonstrated. The results further revealed that teachers have low performance in utilizing varied assessment tools, keeping accurate records, analyzing students' performance and giving feedback, and developing and implementing appropriate activities based on assessment results to promote learning.…”
Section: Introductionmentioning
confidence: 74%
“…the Intermediate Teachers' Institute, Secondary Teachers' Institutes, Intermediate Teachers' Colleges, and Teachers' Colleges. Second, the skills of pre-service and in-service teacher education and training have been promoted and supervised by the Teachers' Colleges (Tawalbeh & Ismail, 2014).…”
Section: Saudi Contextmentioning
confidence: 99%
“…It helps understanding the degree of students' progress towards achieving their learning goals (Linn & Miller, 2005). Classroom instruction is mingled with formative assessment procedures (Tawalbeh & Ismail, 2014;Wiggins & McTighe, 2007). Quiz competitions, questioning techniques, asking for self-reflection, and providing feedback are the kinds of formative assessment (Wiliam & Thompson, 2008).…”
Section: Review Of Literaturementioning
confidence: 99%